Gold rush fever : a story of the Klondike, 1898 - Greenwood, Barbara, 1940- (Kids Can Press, 2001)
Tells the story of thirteen-year-old Tim and his older brother Roy and their adventures traveling to the Klondike in search of gold in 1898; and includes essays that discuss historical events and people associated with the Gold Rush.